2021
DOI: 10.1039/d1ra05948c
|View full text |Cite
|
Sign up to set email alerts
|

Biocidal activity of Ba2+-doped CeO2 NPs against Streptococcus mutans and Staphylococcus aureus bacterial strains

Abstract: The highest antibacterial activity was achieved for Ba-doped CeO2 (BCO) NMs and is suitable for healthcare applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…A substantiated comparison of the inhibition zone diameter with respect to S. aureus and E. coli bacteria monitored in various doped (single or double) ZnO materials is shown in Table 3. From the table, it can be seen that Cd, Ba co‐doped ZnO nanorods prepared show enhanced antibacterial activity as observed in the current study when compared to Cd, Ba co‐doped CuO, 28 Fe, Co co‐doped ZnO, 26 Mn doped ZnO, 58 Ag doped ZnO, 58 Cu doped ZnO, 17 Sn doped ZnO, 17 Ti doped ZnO, 24 Cd doped CuO, 28 Ti doped MgO, 60 and Ba doped CeO 2 51 nanoparticles. The impressive antibacterial activity of Cd, Ba co‐doped ZnO nanoparticles is because of the low crystallite size (42.35 nm), decrease in lattice strain, and increase in dislocation density, as evidenced from the XRD data.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…A substantiated comparison of the inhibition zone diameter with respect to S. aureus and E. coli bacteria monitored in various doped (single or double) ZnO materials is shown in Table 3. From the table, it can be seen that Cd, Ba co‐doped ZnO nanorods prepared show enhanced antibacterial activity as observed in the current study when compared to Cd, Ba co‐doped CuO, 28 Fe, Co co‐doped ZnO, 26 Mn doped ZnO, 58 Ag doped ZnO, 58 Cu doped ZnO, 17 Sn doped ZnO, 17 Ti doped ZnO, 24 Cd doped CuO, 28 Ti doped MgO, 60 and Ba doped CeO 2 51 nanoparticles. The impressive antibacterial activity of Cd, Ba co‐doped ZnO nanoparticles is because of the low crystallite size (42.35 nm), decrease in lattice strain, and increase in dislocation density, as evidenced from the XRD data.…”
Section: Resultssupporting
confidence: 69%
“…In contrast, the absorbance of UVB at 280 and 320 nm for Cd, Ba co‐doped ZnO is found to be 78% and 88%, respectively, whereas the absorbance of UVA at 360 and 400 nm is found to be 97% and 16%, respectively. Moreover, it is unambiguously clear that Cd, Ba co‐doped ZnO exhibits tremendous UV absorption in the wavelength regime 280–360 nm, which indicates the simultaneous UVA and UVB blocking capability, thereby outperforming other UV‐shielding materials such as Fe, Co co‐doped ZnO, 26 Ag doped ZnO, 1 Mn doped ZnO, 4 Na doped ZnO, 6 polymer film N doped ZnO, 15 Sn doped ZnO quantum dots, 16 PVA/CAN doped ZnO, 49 Al doped ZnO/Epoxy nanocomposites, 50 Cd doped CuO, 28 Ba doped CeO 2 , 51 and Ba doped TiO 2 nanoparticles 52 as indicated in Table 2. However, at 280 nm, the blocking percentage of Cd, Ba co‐doped ZnO nanoparticles is lower than Fe, Co co‐doped ZnO and Mn doped ZnO nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Among a heterogeneous variety of NPs, cerium oxide (CeO 2 ) is one of the widely utilized NPs due to its exclusive characteristic features of biocompatibility, stability, eco-friendliness, and eccentric surface chemistry [18,19]. e lattice site of the CeO 2 NPs or nanoceria is capable of producing more oxygen vacancies [20,21] and this redox property can be significantly exploited in the treatment of various ailments related to oxidative stress. It is substantially employed in the production of sensors, catalysts, cells, drug-delivery agents, therapeutical agents, and antiparasitic creams [15,18,22].…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial results showed that Ba-doped ceria had the highest biocidal activity, and this was attributed to it comprising the smallest particles and exhibiting the highest ROS production rate. 45 Na-doped ceria prepared via a cryochemical route in liquid nitrogen with different molar ratios of Na and Ce was tested as a catalyst for CO 2 hydrogenation. 52 The results revealed that the yield of CO produced varies with the Na/Ce ratio used.…”
Section: Metal Doped Ceriamentioning
confidence: 99%
“…Moreover, particle shapes, such as rods and cubes, tend to exhibit better oxygen storage performance than other polyhedrons, such as octahedrons. This oxygen reservoir property also enables ceria to act as a radical scavenger, thus making it a valuable material in the biomedical field . Compared with materials possessing similar band gaps (ZnO and TiO 2 , for example), ceria has a higher oxygen ion mobility and a longer photogenerated charge carrier lifetime, making it superior for certain optical and related applications , Furthermore, ceria is known to be an active oxygen donor in certain reactions, including three-way catalytic (TWC) reactions to decompose toxic components of automobile exhaust, water–gas shift (WGS) reactions at low temperature, oxygen permeation membrane systems, oxygen sensors, and fuel cells.…”
Section: Properties Of Ceriamentioning
confidence: 99%